TRANSFORMASI PARADIGMA PENDIDIKAN ISLAM DALAM MERESPONS REALITAS MULTIKULTURAL INDONESIA - Amri, Irbab Aulia; Husna, Muhammad Ahsanul; Imron, Ali (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Islamic education plays a strategic role in responding to the multicultural reality of Indonesian society, which is characterized by religious, cultural, and social diversity. The challenges faced by Islamic education extend beyond strengthening religious identity to include its capacity to foster inclusive, tolerant, and just attitudes within a pluralistic society. This study examines the transformation of Islamic education in promoting multiculturalism in Indonesia through a library-based research approach. The analysis focuses on three main aspects: paradigms of Islamic education within a multicultural context, multicultural values embedded in Islamic education, and forms of transformation in Islamic education that address social diversity. The study employs a library research method by analyzing academic books and scholarly articles related to Islamic education and multiculturalism. Data are examined using content analysis to identify key concepts, patterns of thought, and prevailing approaches in Islamic education’s response to multiculturalism. The findings indicate that Islamic education is normatively grounded in values that align with the principles of multiculturalism, including justice, tolerance, and human solidarity. The transformation of Islamic education therefore requires a paradigm shift toward more inclusive approaches, the development of curricula that are responsive to diversity, and the implementation of dialogical and reflective pedagogical practices. This study underscores that a systemic and integrated transformation of Islamic education is a crucial prerequisite for strengthening its role in fostering a multicultural Indonesian society.